Oral squamous cell carcinoma outcome in adolescent/young adult: Systematic review and meta‐analysis. Issue 2 (22nd November 2021) - Kaminagakura, Estela; Tango, Rubens Nisie; Cruz‐Perez, Danyel; Bonan, Roberta; Yamamoto de Almeida, Luciana; de Almeida Lança, Maria Letícia; Bonan, Paulo; Martins, Hélder; Takahama, Ademar; Ito, Fábio Augusto; Coutinho‐Camillo, Cláudia Malheiros; Lourenço, Silvia Vanessa; et al.
Abstract: To perform a systematic review focusing on the prognosis of oral cavity squamous cell carcinoma (OSCC) in young patients (≤40 years old) compared to older (>40 years old). Four databases were used in our search strategy. First, all titles were systematically organized using the Covidence platform online. In the second phase, 118 full texts of potentially eligible studies were analyzed by reviewers independently and in pairs. Twelve studies were considered eligible for data extraction. The relapse was higher in the young than in controls (pooled relative risk (RR) = 1.31; 95% CI [1.10–1.56]). The 5‐year disease‐free survival (DFS) was worse in young group (pooled hazard ratio (HR) = 0.73; 95% CI [0.63–0.85]) but the 5‐year overall survival (OS) estimate was similar between the groups (pooled HR = 0.84; 95% CI [0.70–1.00]). While the 5‐year OS was similar between groups, the number of relapses and 5‐year DFS were worse in patients with OSCC ≤40 years old.